Studies on antibacterial activity of extracts from Tinospora cordifolia (Giloy) against Staphylococcus aureus - Deepika; Padma Singh; Vishal Upadhayay (Environment Conservation Journal, 2009)
The active  components  of stem  bark  of Tinospora cordifolia  were extracted  using  cold  water  and organic  solvents  (methanol,   diethyl  ether and  acetone)  and  were  tested  against  Staphylococcus aureus  using the agar disc diffusion  method.  All  the four extracts  inhibited  the growth of S.   aureus, with  methanol  extract  exerting the  highest  activity whereas  water  extract was  least active.  The results  were  compared  with  the  reference  antibiotic ciprofloxacin